Historum (History Forum): Eksistensi Warisan Sejarah Dan Kearifan Lokal Dalam Tradisi Melaro Desa Redang Kecamatan Rengat Barat - Zulfurqon, Zulfurqon; Wahyuni, Nuriyah; Rahmawati, Astri; Asmawati, Asmawati; Rahayu, Heppy Sri; Hasanah, Ella Nur; Lubis, Dhea Annisa; Ariyanti, Rara Fitri; Luthfia, Hafizha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
One of the Kukerta MBKM UNRI service activities is carried out through Historum (History Forum) by highlighting and popularizing local traditions, namely the Melaro Tradition in Redang Village. The Melaro tradition is the local culture of Redang Village which must be preserved by fostering a sense of pride in the local traditions that are owned and requires participation from the community around Redang Village. This service uses a descriptive research study with qualitative research methods with primary data sources, namely interviews with traditional elders in four hamlets in Redang Village. The interview data obtained will be compiled and made into an infographic. Secondary data sources were obtained from several research journals. Data collection techniques are carried out using observation, interviews and documentation. The results of the service show that preserving the Melaro tradition with Historum can provide awareness of the importance of protecting the environment where the Melaro Tradition is carried out. Historum's role by involving traditional elders, village administrators and the community around Redang Village can provide positive things in the form of a perspective on the importance of preserving the Melaro tradition. So that it can provide awareness of the importance of protecting the environment and preserving local wisdom and fostering a sense of love for the environment in order to maintain the environment and the existence of the Melaro Tradition in Redang Village.